Clinical application status of plum blossom needle technique in nursing care of myopia patients (梅花针技术治疗近视的临床应用及护理) - LI Jinhuan (李金环); YIN Kexin (尹可欣) (中西医结合护理)
Plum-blossom needle therapy for myopia has the advantages of remarkable efficacy, easy-to use operation, convenience in practical use, and reduced adverse reactions. It has good effects in relieving various disease symptoms. This study summarizes and analyzes the mechanism of plum blossom needle therapy, the basis for selecting acupoints, the current application status of combined acupuncture, auricular acupressure, thunder-fire moxibustion and other methods in clinical practice, as well as the nursing strategies related to plum blossom needle, in order to provide a basis for further research on the standardization and operability of plum blossom needle technology in the treatment of myopia. (梅花针疗法具有疗效确切、操作简便、方便实用、不良反应少等优势, 在缓解诸多疾病症状方面具有较好的效果。本研究就梅花针治疗近视的作用机理、临床应用进展和护理对策进行综述, 旨在为临床中进一步探究梅花针技术治疗近视的规范性和可操作性提供参考。)